Scientific Publishing and the Commitments of Researcher Communities - López-López, Wilson (2014)
Journals have dynamics associated to editorial quality, content quality, visibility, accessibility, communication and economic sustainability. When these dimensions of editorial management work, journals grow in an homogenous fashion (López, Silva, García-Cepero, Bustamante, & López, 2011). However, journals in Latin America do not flow in that way, because they depend on supporting institutions, research communities, and knowledge users. Institutional publications do not have the necessary infrastructure, management or financial conditions to cover all the aspects involved in producing a journal. Research communities in Latin America are still learning communication, visibility and diffusion practices, despite efforts to increase cooperation amongst researchers in Latin America (Vera-Villarroel, Lillo, López-López, & Silva, 2011). Finally, several bibliometric indicators suggest that our communities in Iberoamerica normally go to the North American and European literature, and the knowledge produced in our region is still underused (López et al., 2011). In this region, editors and publishing institutions have been learning the demands of editorial management for some time, they have enrolled in qualification processes, we have commenced to understand how Open Access, scientometric indicators, filing technologies, and content management systems work. We are still learning how to locate and track reviewers, how to be patient with the editorial teams (which they are learning too). We have also come to learn that a sizable part of this process does not depend exclusively on us, but also on other entities, so we need to accept a certain loss of control over some of the editorial management process. We also need to acknowledge that we do not always make the right decisions and that our academic decisions are not always the best ones. On top of that, we need to rapidly learn that our now open-access journals are visible to reviewers, students and professionals all over the world, from different fields. Our knowledge has the potential to have an impact on society because lay communities have now access to that knowledge. In the following weeks, we will attend the global event on Open Access as a movement that transcends publications and impacts education, policy and research itself (Open Science Collaboration, 2012). The success or failure of our task is reflected in many ways. For example, in the confidence and reputation given to us by communities, and that we need to return with content quality. It is a highly complex task, though, and when researchers give us power, they also increase our workload in terms of manuscripts to be reviewed. The growth in the amount of published articles needs to come together with an increase in citations so that visibility indicators do not go down. Authors need to be involved, since the reputation of journals depends on the quality and the use of these contents. Some journals have been known to decrease the number of articles they publish as a way to protect themselves from a possible drop of the impact factors. Universitas Psychologica accepts the challenge of promoting the visibility of our communities, of fostering dialogue and synergies within them. This effort cannot be rewarded if the researchers themselves and the communities they are in do not use this knowledge. The path we selected, enhancing visibility in our contexts, is in the hands of the communities themselves. Rather than artificially increasing impact indicators, we want to grow realistically and this long-term project depends, above all, on the relationships amongst researchers. Wilson López López